Responsabilidad patronal de la retención de aportaciones a la Seguridad Social y su incidencia en los derechos constitucionales de los trabajadores - Salazar Esquivel, Diógenes Atahualpa (2016)
This work of legal research, it is done in order to reform the Art. 242 of the Organic Code Integral Criminal guaranteeing the rights of workers set out in the Standard Constitution, so that they will not retain the contribution to the Social security, which corresponds to all persons performing their lawful and personal services under dependence on the employer either public or private, which is intended to benefit, this segment of the population so that some feel member and manager of the employment generation Ecuador, whose only desire is to improve their personal and family economic situation. Although in the Constitutional Charter and case law recognizes the principles of equality and indispensability, labor escalation, among other principles that protect the right to work as legally protected and priority attention, the above laws are ineffective when resolve situations where labor rights of workers transgresses, which in many cases are people from vulnerable groups such as older adults, this project of legal research can be felt how the employer has generated the effect on these Constitutional principles that invests working class. In the country there is no culture of adequate protection of workers' rights, in reality workers are not recognized labor rights fully being victims of labor exploitation and illegal exploitation of the labor force; which it is considered by the respective reform relevant Code of Criminal Integral for the rights of workers in relation to the employer contributions. Immutable abuses are obvious suffering labor class, where several times their rights are violated. Notoriously we can show that violates the law covers and protects, is the result of a current legal system suffers from many loopholes and actually hurt the working class. The lack of rigorous sanction helps employers adversely affects the rights of the working class.